Effects of Alarm Modality and Alarm Reliability on Workload, Trust, and Driving Performance. (September 2015) - Shah, Smruti J.; Bliss, James P.; Chancey, Eric T.; Brill, J. Christopher
As roads are getting more congested, the rate of automobile crashes due to driver error is also rising. Driving is an attention demanding task. The automobile industry has developed collision avoidance warning systems to increase situation awareness and roadway safety. Different modalities of alarms could be used to increase drivers' situation awareness. The current study is a preliminary analysis of the effects of alarm reliability (70% & 90%) and alarm modality (auditory & tactile) on driver performance, trust in alarms, and perceived workload. Participants ( n =5) drove in a simulated environment. The results showed that drivers had fewer collisions in the tactile condition than the auditory condition. The findings of this research can inform which alarm modality is effective in improving driver performance and how practitioners can use this information to improve collision avoidance warning systems to increase roadway safety.